NOX4–TIM23 interaction regulates NOX4 mitochondrial import and metabolic reprogramming - Pandey, Jyotsana; Larson-Casey, Jennifer L.; Patil, Mallikarjun H.; Joshi, Rutwij; Jiang, Chun-sun; Zhou, Yong; He, Chao; Carter, A. Brent (The Journal of biological chemistry, 2023)
Pulmonary fibrosis is a progressive lung disease characterized by macrophage activation. Asbestos-induced expression of nicotinamide adenine dinucleotide phosphate hydrogen oxidase 4 (NOX4) in lung macrophages mediates fibrotic progression by the generation of mitochondrial reactive oxygen species (ROS), modulating mitochondrial biogenesis, and promoting apoptosis resistance; however, the mechanism(s) by which NOX4 localizes to mitochondria during fibrosis is not known. Here, we show that NOX4 localized to the mitochondrial matrix following asbestos exposure in lung macrophages via direct interaction with TIM23. TIM23 and NOX4 interaction was found in lung macrophages from human subjects with asbestosis, while it was absent in mice harboring a conditional deletion of NOX4 in lung macrophages. This interaction was localized to the proximal transmembrane region of NOX4. Mechanistically, TIM23 augmented NOX4-induced mitochondrial ROS and metabolic reprogramming to oxidative phosphorylation. Silencing TIM23 decreased mitochondrial ROS and oxidative phosphorylation. These observations highlight the important role of the mitochondrial translocase TIM23 interaction with NOX4. Moreover, this interaction is required for mitochondrial redox signaling and metabolic reprogramming in lung macrophages.